The Relationship Between Lila Size and Mother's Weight Gain During Pregnancy with the Birth Weight of the Baby at the Atikah Sipolu–polu Midwife Clinic, Panyabungan District, Mandailing Regency City Christmas 2023 - Nasution, Intan Angriani Ananda; Puspita, Rania (Cattleya Darmaya Fortuna, 2023)
During pregnancy, the nutritional needs of expectant mothers increase significantly to support both their own health and the development of the fetus. In situations where maternal food intake is limited, the fetus continues to draw from the mother's nutritional resources, potentially leading to maternal malnutrition and imbalanced food consumption. Such conditions can result in adverse outcomes such as premature birth or even fetal demise, as well as prolonged labor during childbirth. Hence, comprehensive maternal health assessments before delivery are crucial. This study aims to investigate the relationship between maternal weight gain during pregnancy, maternal upper arm circumference (MUAC), and newborn weight at the Atikah Sipolu-Polu Midwife Clinic in the Panyabungan District, Mandailing Natal Regency, in 2023. A descriptive research design with a cross-sectional approach was employed. The study population consisted of mothers who delivered at the Atikah Sipolu-Polu midwife clinic, with a total sample size of 45 individuals selected through total sampling. Data were collected using both primary and secondary sources. The analysis utilized the chi-square test with a significance level set at p<0.05. The results indicate a significant relationship between MUAC size, maternal weight gain during pregnancy, and newborn weight, with a calculated p-value of 0.001 (p < 0.05). This study underscores the importance of enhancing nutritional patterns, particularly during pregnancy. It emphasizes the necessity for pregnant women to consume a balanced diet comprising vegetables, fruits, meats, vitamins, and other essential nutrients to ensure optimal maternal and fetal health outcomes.